A Suggested Ethical Framework for Evaluating Corporate Mergers and Acquisitions - Chase, Daniel G. (Journal of business ethics, 1997)
The 1980s witnessed a dramatic increase in hostile takeovers in the United States. Proponents argue that well- planned mergers enhance the value of the firm and the value of the firm to society. Critics typically argue that undesired takeovers ultimately harm society due to external costs not borne by the acquiring firm. To be socially responsible, the manager must consider the effects of the merger/acquisition on all stakeholders. Different traditional ethical frameworks for decision making are proposed and reviewed. A model is proposed.